ANTIPROLIFERATIVE AND ANTIOXIDANT ACTIVITY OF LEAVES EXTRACTS OF MORINGA OLEIFERA - Sanganna, Burli; Chitme, Havagiray R.; Vrunda, Khanvilkar; Jamadar, Mohsin J. (International Journal of Current Pharmaceutical Research, 2016)
Objective: The aim of the study was to investigate the ethanolic and aqueous extract of leaves of Moringa oleifera for phytochemical constituents, antiproliferative and antioxidant activity. Methods: The ethanolic extract of leaves of Moringa oleifera, belonging to the family Moringaceae was prepared by using soxhlet apparatus and aqueous extract was prepared by using maceration process. The extract was evaluated for its phytochemical constituents. The antiproliferative effects of both extracts were checked by using MTT ([3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide]) assay on HT-29 colon cell line and the antioxidant activity were checked by using DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. In antiproliferative and antioxidant activity the 5-FU (5-fluro uracil) and Ascorbic acid used as a standard drug for present results conclusion respectively. Results: The results obtained in MTT assay shown that ethanolic extract of Moringa oleifera had a more potent antiproliferative effect (growth inhibition of 62.25% at 100 Î¼g/ml) on HT-29 colon cell line as compared to aqueous extract (% growth inhibition of 27.86 at 100 Î¼g/ml) of Moringa oleifera. The ethanolic extract of Moringa oleifera shown more potent antioxidant activity (% inhibition of ethanolic 75.57 at 100 Î¼g/ml) than aqueous extract (38.16 at 100 Î¼g/ml) of Moringa oleifera. The activity shown by the extract is concentration dependent. Conclusion: In the present study we have investigated that the effect of ethanolic and aqueous leaves extracts of Moringa oleifera possess antiproliferative and antioxidant properties.